On stabilizing index and cyclic index of certain amalgamated uniform hypergraphs - Ku, Cheng Yeaw (2024)
Let G be a connected uniform hypergraph and A(G) be the adjacency tensor of G. The largest absolute value of the eigenvalues of A(G) is called the spectral radius of G. The number of eigenvectors of A(G) associated with the spectral radius is called the stabilizing index of G. The number of eigenvalues of A(G) with modulus equal to the spectral radius is called the cyclic index of G. In this paper, we consider a class of amalgamated uniform hypergraphs and compute its stabilizing index and cyclic index.